Proportional influence? Electoral rules and special interest spending - Marko Köthenbürger; Peter Egger; Michael Smart (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Conventional wisdom has it that proportional representation leads to more coalition governments and so to greater government spending, especially in redistributive categories favoured by special-interest groups. In contrast, we show in a theoretical model that first-past-the-post systems of government may give special interests greater influence in the winning electoral coalition than they would have in the corresponding legislative coalition under proportional representation. Evidence from a quasi-experimental reform in German local government supports this view. Introduction of a mayor directly elected under first-past-the-post rules caused a significant increase in local government expenditure, particularly in redistributive spending categories.
Keywords: H20; D72; H11; 330